Polyethenetetrathiolate or polytetrathiooxalate? Improved synthesis, a comparative analysis of a prominent thermoelectric polymer and implications to the charge transport mechanism. Issue 36 (14th August 2018) - Tkachov, Roman; Stepien, Lukas; Grafe, Robert; Guskova, Olga; Kiriy, Anton; Simon, Frank; Reith, Heiko; Nielsch, Kornelius; Schierning, Gabi; Kasinathan, Deepa; Leyens, Christoph
Abstract : Polymerisation of the "true monomer" results in a high quality product with improved and good reproducible characteristics. Abstract : 1, 1, 2, 2-Ethenetetrathiolate (ett 4− ) coordination polymers, such aspoly[K x (Ni-ett)], have been known for decades for their excellent thermoelectric properties. However in reality, ett 4− is neither a "true" comonomer which participates in the polymerization, nor represents a "true" repeat unit of the target polymer. Indeed, poly[K2 (Ni-ett)], which is formally the product of Ni-induced polymerization ofett 4−, has a poor conductivity and needs to be oxidized to show attractive thermoelectric characteristics. The polymerization and oxidation processes are poorly controllable which causes irreproducibility of the polymer properties. To improve the synthesis reproducibility, we studied polymerization of potassium tetrathiooxalate (K2 tto ), the convenient synthesis of which was developed in our recent work. BecauseK2 tto is the "true monomer", and not its precursor, a high quality product is reproducibly formed simply by mixingK2 tto with NiCl2 at room temperature. The procedure does not require additional components (bases), or special conditions (prolonged heating), which are usually needed for the preparation of this polymer from the monomer precursor 1, 3, 4, 6-tetrathiapentalene-2, 5-dione (TPD ). Furthermore, astto 2− is formally the product of two-electron oxidation ofett 4−, the poorly controllable oxidation process is avoided andpoly[Ni-tto] almost free from K is directly formed upon the complexation ofNi 2+ andtto 2− . Thus-obtainedpoly[Ni-tto] possesses conductivity in the range of 27–47 S cm −1 and a Seebeck coefficient in the range of −38 to −55 μV K −1, which are superior thermoelectric properties compared topoly[K x (Ni-ett)] samples obtained by the previously reported methods. Redox and structural properties ofpoly[Ni-tto] were compared with those ofpoly[K x (Ni-ett)] obtained by the reported methods. Furthermore, DFT calculations were performed to shed more light on generally promising properties of this class of materials. Particularly, possible packing models have been predicted for polymers, and the molecular dynamics simulations have been used to simulate the molecular arrangements under ambient conditions.